توجيه القراءات عند مجير الدين العليمي رحمه الله في تفسيره فتح الرحمن في تفسير القران .سورة البقرة أنموذجا. - اسماعيل, بن فرج الله; سعد الدين, زوزو (University of eloued جامعة الوادي, 2021)
"ملخص الحمد لله والصلاة والسلام على رسول الله أما بعد فهذا البحث بعنوان توجيه القراءات عند مجير الدين العليمي من خلال تفسيره فتح الرحمن في تفسير القران-سورة البقرة أنموذجا- وهو يطرح الاشكال، مامعنى توجيه القراءات ومن هو المفسر مجير الدين العليمي، ومامنهجه المتبع في تفسيره وفي إيراده للقراءات القرانية وكيف وظف صور التوجيه في شرح وبيان معان القران الكريم. فكان إجابة ذلك ضمن خطة بحثية؛ انتظمت بمبحثين تحتهما مطالب ثم فروع، فالمبحث الاول نظري، خصصناه بتعريف بتوجيه القراءات ومايتعلق به من نشأة وأدوات وأنواع وأشهر ماصنف فيه، وترجمة موجزة للإمام مجير الدين العليمي من خلال ذكر حياته الشخصية والعلمية، وتعريفا بكتابه""فتح الرحمن"" والتحقق من اسمه ونسبته اليه مع وصف منهجه في تعامله مع القراءات ومصادره في التفسير. أما المبحث الثاني تطبيقي يعتبر لُبّ الدراسة، درسنا النماذج التي فيها توجيه القراءات القرانية التي وجهها العليمي سواء قراءات لهجات أو معان، من خلال سورة البقرة فدرسناها على ضوء أنواع التوجيه الصرفي النحوي البلاغي الفقهي وباللهجات العربية وبأحكام التجويد سعينا من وراء ذلك تتبع واستقراء مواضع توجيهاته بشيء من التحليل والموازنة مع غيره من المفسرين والموجهين للوقوف على التوجيه الصحيح ماأمكننا ذلك. فتوصلنا في الاخير مايلي: .أن علم توجيو القراءات ليس كغيره من العلوم، فهو ركيزة المف سر في الكشف عن مدلولات ومعان ألفاظ القران العظيم .مجير الدين العليمي إمام ومف سر و مؤ رخ، خدم ال دين، اقتفى أثر سلفو في التعليم والتعلم. .حفل تفسير مجير الدين العليمي بتوجيو القراءات القرآنية المتواترة مع عزو من قرأ بها وذكر صور توجيهها اللغوي، البلاغي، اللهجات العربية وأحكام التجويد،.. دون إنتصار أو دحض. .من مميزات تفسيره بسهولة العبارة، الايجاز، التفسير بالمأثور، المسائل النحوية والصرفية، الاخبار والقصص، الاحكام الفقهية والعقدية...إلخ""Summary Praise be to God, and prayers and peace be upon His Messenger, God, as for what follows This research is entitled “Guiding readings for Mujir Al-Din Al-Alimi through his interpretation” “Fath Al-Rahman in the interpretation of the Qur’an - Surat Al-Baqarah as a model - and it raises the problem, what is the meaning of directing the readings and who is the interpreter Mujir Al-Din Al-Alimi, and what is his approach in his interpretation and in his reference to the Qur’anic readings, and how he was used Pictures of guidance in explaining and clarifying the meanings of the Holy Qur’an. The answer to this was within a research plan; It was organized into two sections under which demands and then branches. The first topic is theoretical. We devoted it to a definition of directing the readings and what is related to it in terms of origin, tools, types and the most famous of what was classified in it, and a brief translation of Imam Mujir al-Din al-Alimi by mentioning his personal and scientific life, and an introduction to his book “Fath al-Rahman” and verification of his name and lineage to him with a description of his approach in dealing with readings and his sources in interpretation. As for the second applied topic, it is considered the core of the study. We studied the models in which the Quranic readings were directed by Al-Alimi, whether readings of dialects or meanings, through Surat Al-Baqarah. We studied them in the light of the types of guidance; The morphological, the grammatical, the rhetorical, the jurisprudence, and the Arabic dialects and the rulings of intonation, we sought from that to follow and extrapolate the places of his directives with some analysis and Maronites with other commentators and guides, to find out the correct guidance as much as we could. We finally got the following: *The science of directing readings is not like other sciences, as it is the basis of the exegete in revealing the meanings and meanings of the words of the Great Qur’an. *Mujir Al-Din Al-Alimi is an imam, interpreter and historian, who served the religion, following the trail of his predecessor in teaching and learning. *Mujir al-Din al-Alimi’s interpretation ceremony by directing the frequent Qur’anic readings with attributing those who read them and mentioning the images of their linguistic, rhetorical guidance, Arabic dialects and the provisions of intonation, .. without victory or refutation. *Among the advantages of its easy interpretation are phrases, brevity, interpretation of the proverb, grammatical and morphological issues, news and stories, jurisprudence and doctrinal rulings...etc."
لغة ودراسات
Keywords: توجيه القراءات القرانية.مجير الدين العليمي رحمه الله.تفسيره "فتح الرحمن في تفسير القران".سورة البقرة أنموذجا.; Directing Quranic readings. Mujir Al-Din Al-Alimi, may God have mercy on him. His interpretation of "Fath al-Rahman in the interpretation of the Qur'an". Surat Al-Baqarah as a model.